Bakhtin and native language teaching in Brazil: some perspectives - Campos, Maria Inês (Revista Conexão Letras, 2016)
The purpose of this article is to examine the infl uence of Bakhtinian theory, in particular the concept of speech genre, in offi cial documents of the Ministry of Education inBrazilintended for teachers in the public and private networks. In order to understand this very important impact of Bakhtin and the Circle, several aspects of how the works that were the hallmark of government guidance were received will be revisited. The outcome will be supplemented by analyzing a chapter of a textbook in the native language for high school students that deals with the concept of genre in teaching the production of argumentative texts.